Pancreatoduodenectomy (PD) and postoperative pancreatic fistula (POPF): A systematic review and analysis of the POPF-related mortality rate in 60, 739 patients retrieved from the English literature published between 1990 and 2015. Issue 19 (May 2017) - Pedrazzoli, Sergio
Abstract: Background: Pancreatoduodenectomy (PD) is one of the most technically demanding operations challenging surgeons, and a postoperative pancreatic fistula (POPF) can complicate an otherwise uneventful postoperative (PO) course. This review examined the methods and procedures used to prevent postoperative pancreatic fistula (POPF) after pancreatoduodenectomy (PD). Methods: A comprehensive systematic search of the literature was performed using PubMed (Medline), Embase, Web of science, and the Cochrane databases for studies published between January 1, 1990 and December 31, 2015. English language articles involving at least 100 patients undergoing PDs carried out in centers performing at least 10 PDs/y were screened for data regarding the Grade of any POPFs according to the definition of the International Study Group on Pancreatic Fistula (ISGPF) and the overall rate of PO mortality related to POPF. Results: We reviewed 7119 references through the major databases, and an additional 841 studies were identified by cross-checking the bibliographies of the full-text articles retrieved. After excluding 7379 out of 7960 studies, because they did not meet the eligibility criteria, the full texts of 581 articles were examined; 96 studies were excluded at this point, because they concerned partially or totally duplicate data that had already been reported. The remaining 485 articles were screened carefully for POPF-related mortality and POPF Grades as defined by the ISGPF. Of the 485 articles, 208 reported the POPF-related PO mortality rate and 162 the Grades (A, B, and C) of POPFs in 60, 739 and 54, 232 patients, respectively. The POPF-related mortality rates after pancreatojejunostomy and pancreatogastrostomy were similar but were less (0.5% vs. 1%; P  = .014) when an externally draining, trans-anastomotic stent was placed intraoperatively. The incidence of the different Grades of POPF Grade was quite variable, but Grade C POPFs were associated with a PO mortality rate of 25.7% (range 0–100%). Conclusions: The POPF-related mortality rate has remained at approximately 1% over the past 25 years. Only externally draining, trans-anastomotic stents decreased the POPF-related mortality rate. However, adequately designed venting drains were never tested in randomized controlled trials (RCTs).